Development of small diameter pilot hole directional drilling for trenchless utility installation; IOP Conference Series: Earth and Environmental Science; Vol. 43 : Problems of Geology and Subsurface Development - Saruev A. L. Aleksey Lvovich (Latest Technologies in Oil and Gas Driling, 2016)
Title screen